Re-thinking Freire : globalization and the environmental crisis - Bowers, C. A.; Apffel-Marglin, Frédérique (Sociocultural, political, and historical studies in education., 2005)
This collection of essays by Third World activists highlights two major world changes which, they argue, have been neglected by Freire and his many followers: the Third World grass-roots cultural resistance to economic globalization, and the ecological crisis.